2018
DOI: 10.1002/anie.201800367
|View full text |Cite
|
Sign up to set email alerts
|

Chelating N‐Heterocyclic Carbene Ligands Enable Tuning of Electrocatalytic CO2 Reduction to Formate and Carbon Monoxide: Surface Organometallic Chemistry

Abstract: Reported here is the chelate effect as a design principle for tuning heterogeneous catalysts for electrochemical CO reduction. Palladium functionalized with a chelating tris-N-heterocyclic carbene (NHC) ligand (Pd-timtmb ) exhibits a 32-fold increase in activity for electrochemical reduction of CO to C1 products with high Faradaic efficiency (FE =86 %) compared to the parent unfunctionalized Pd foil (FE=23 %), and with sustained activity relative to a monodentate NHC-ligated Pd electrode (Pd-mimtmb ). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 49 publications
2
111
1
Order By: Relevance
“…AT afel slope of 123 mV/ decade is observed for OAm-AuNP,w hich is comparable to what is expected for rate-determining single-electron transfer (120 mV/decade) from adsorbed CO 2 to generate the surface adsorbed CO 2 C À . We then calculated the possible pathways of CO 2 reduction into CO on both models.Inparticular,the total energy of each surface model was computed and converted to free energy at 25 8 8C, 1atm, and À0.11 V, the theoretical equilibrium potential of CO 2 reduction into CO [33,42] (details in Supporting Information). [28,31] Finally,w eu tilized density functional theory (DFT) and computational hydrogen electrode calculations on two models of Au(111) and P1-Au(111) (Supporting Information, Figure S11) to further probe the effects of porphyrin ligation on the Au surfaces and its reactivity consequences.W ef irst found that the adsorption of CO 2 on these two models is energetically favored, as evidenced by their adsorption energy of À0.29 eV for Au (111) and À0.68 eV for P1-Au(111) (Supporting Information, Figure S12).…”
mentioning
confidence: 99%
“…AT afel slope of 123 mV/ decade is observed for OAm-AuNP,w hich is comparable to what is expected for rate-determining single-electron transfer (120 mV/decade) from adsorbed CO 2 to generate the surface adsorbed CO 2 C À . We then calculated the possible pathways of CO 2 reduction into CO on both models.Inparticular,the total energy of each surface model was computed and converted to free energy at 25 8 8C, 1atm, and À0.11 V, the theoretical equilibrium potential of CO 2 reduction into CO [33,42] (details in Supporting Information). [28,31] Finally,w eu tilized density functional theory (DFT) and computational hydrogen electrode calculations on two models of Au(111) and P1-Au(111) (Supporting Information, Figure S11) to further probe the effects of porphyrin ligation on the Au surfaces and its reactivity consequences.W ef irst found that the adsorption of CO 2 on these two models is energetically favored, as evidenced by their adsorption energy of À0.29 eV for Au (111) and À0.68 eV for P1-Au(111) (Supporting Information, Figure S12).…”
mentioning
confidence: 99%
“…[3] Theo ne-electron reduction of CO 2 occurs only at very cathodic potential values,m ainly because of the energy penalty associated with bending of the linear molecule upon electron uptake to furnish the [CO 2 ]C À radical. [7][8][9][10] Since the advent of frustrated Lewis pair (FLP) chemistry, increasing efforts have been devoted to the replacement of transition-metal catalysts by appropriate combinations of main-group Lewis acids and bases.I nt he context of CO 2 activation, ap lethora of capture products such as R 3 P-C(O)-O-BR' 3 are nowadays known. [1a] Some transition-metal com-pounds can act as nucleophiles toward CO 2 molecules and thereby transfer two electrons simultaneously onto the substrate,w hich is afterwards stabilized through p backbonding (see below).…”
mentioning
confidence: 99%
“…Recent works by Crudden and co‐workers demonstrate that NHCs are excellent ligands for the functionalization of metal electrodes and the resulting gold/NHCs surfaces exhibit much higher stability with respect to the conventional gold/thiolate surface . Stimulated by these results, a flexible tripodal NHC ligand 7 was recently reported by Wen and Chang, which was used to modify palladium electrode (Figure ) . The binding mode of the resulting Pd/ 7 surface was supported by X‐ray photoelectron spectroscopy (XPS), FRIT, and 13 C NMR techniques.…”
Section: Tripodal Anchorsmentioning
confidence: 86%
“… Tripodal NHC ligand 7 and the schematic representation of the palladium electrode surface modified with 7 (Pd/ 7 ). Reprinted with permission from reference . Copyright 2018 Wiley‐VCH Verlag GmbH & Co.…”
Section: Tripodal Anchorsmentioning
confidence: 99%